2020
DOI: 10.1016/j.addbeh.2019.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Measurement invariance across young adults from Hong Kong and Taiwan among three internet-related addiction scales: Bergen Social Media Addiction Scale (BSMAS), Smartphone Application-Based Addiction Scale (SABAS), and Internet Gaming Disorder Scale-Short Form (IGDS-SF9) (Study Part A)

Abstract: Measurement invariance across young adults from Hong Kong and Taiwan among three internet-related addiction scales: Bergen Social Media Addiction Scale (BSMAS), Smartphone Application-Based Addiction Scale (SABAS), and Internet Gaming Disorder Scale-Short Form (IGDS-SF9) (Study Part A)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
125
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 174 publications
(166 citation statements)
references
References 54 publications
21
125
0
2
Order By: Relevance
“…The BSMAS has shown good validity and reliability in previous research (Andreassen et al 2016;Andreassen et al 2017;Bányai et al 2017;Lin et al 2017;Monacis et al 2017). The scale has shown measurement invariance across two Chinese cultural areas (Leung et al 2020), as well as time invariance (Chen et al 2020). In the present study the Cronbach's alpha reliability coefficient was .77.…”
Section: Instrumentssupporting
confidence: 52%
See 1 more Smart Citation
“…The BSMAS has shown good validity and reliability in previous research (Andreassen et al 2016;Andreassen et al 2017;Bányai et al 2017;Lin et al 2017;Monacis et al 2017). The scale has shown measurement invariance across two Chinese cultural areas (Leung et al 2020), as well as time invariance (Chen et al 2020). In the present study the Cronbach's alpha reliability coefficient was .77.…”
Section: Instrumentssupporting
confidence: 52%
“…While the names "Bergen Social Media Addiction Scale" and "Bergen Social Networking Addiction Scale" are used interchangeably in the literature (Andreassen et al 2017;Andreassen et al 2017), we use in the following "social networking sites" as social media and social networking sites reflect similar but yet distinct phenomena (see Kuss and Griffiths 2017). The psychometric robustness of the BSMAS has been examined in Italian (Monacis et al 2017), Hungarian (Bányai et al 2017), Persian (Lin et al 2017), and Chinese (Leung et al 2020;Chen et al 2020) samples, where it has showed good properties. Although previous studies have used a variety of methods to examine this scale, there is currently no study that has investigated the psychometric properties of the BSMAS in comparison to the BFAS.…”
Section: Bergen Social Media Addiction Scale and Bergen Facebook Addimentioning
confidence: 99%
“…BSMAS scores correlated with IGDS9-SF scores and assessments of anxiety and depression [34]. The BSMAS has been previously validated among Hong Kong participants [45,46]. The internal consistency of the BSMAS in the present study was 0.83.…”
Section: The Bergen Social Media Addiction Scale (Bsmas)supporting
confidence: 50%
“…The IGDS9-SF has demonstrated high internal consistency (α = 0.87) and low floor or ceiling effects [44]. The IGDS9-SF has also been validated among Hong Kong participants [45,46]. The internal consistency of the IGDS9-SF in the present study was 0.91.…”
Section: Internet Gaming Disorder Scale-short Form (Igds9-sf)supporting
confidence: 50%
“…Moreover, two Hong Kong students were removed from the analyses because they wanted their data removed from the follow-up study. They clearly indicated that their data could be used in a previously related study (i.e., Leung et al, 2019) but not in the present study. More specifically, the previous study used baseline data to establish the measurement invariance of the three studied instruments (i.e., SABAS, BSMAS, and IGDS-SF9) across Hong Kong and Taiwan university students (Leung et al, 2019).…”
Section: Igds-sf9)mentioning
confidence: 59%